Stress, coping, and mental health status among nursing students at a private university in Nakhon Pathom, Thailand - Stephanie Molina; Sarah Jane Racal (GHMJ (Global Health Management Journal), 2018)
Background: Stress, especially among young people, leads to life-threatening mental conditions such as depression and suicide. Nursing students, in particular, are exposed to different kinds of stress such as pressures from both academic and clinical exposures coupled with expectations to succeed. These stressors influence individual coping styles which may eventually affect students' mental, physical, and over-all wellbeing leading to the decline in their learning and academic performance.Aims: This descriptive-correlational study was aimed at exploring the relationships among stress, coping, and mental health status among nursing students at a private university in Nakhon Pathom, Thailand.Methods: Using a systematic random sampling, a descriptive cross-sectional study was done among one hundred and fifty 3rd and 4th year nursing students under the international nursing program. The Perceived Stress Scale, Brief COPE, and the General Health Questionnaire were used to assess the level of stress, the coping strategies used, and the mental health status of the respondents. Descriptive statistics, t-test, and Pearson's correlation were used to answer the research questions.Results: It revealed that the nursing students had moderate level of perceived stress, used acceptance as the most common form of coping, and substance use and denial as the least used. Furthermore, the respondents had mild level of mental health related illness. Significant gender differences were found in the perceived level of stress, and use of coping strategies. While mental health status significantly differed according to year level and interest in nursing. Significant mild to moderate relationships were found among perceived stress level, coping strategies, mental health status, and selected socio-demographic variables.Conclusion: The findings of the study provide additional useful information on the relationships of stress, coping, and health outcomes. Results can also be useful in creating a stress management program for nursing students such as awareness on individual stress response and reinforcing the use of healthy coping strategies. Keywords: Stress, Coping, Mental Health, Nursing students, Thailand Received: 08 August 2018, Reviewed: 10 September 2018, Received: in revised form 17 October 2018, Accepted: 21 October 2018 DOI: 10.35898/ghmj-23557